Identification and determination α and β-acids from Columbus hops using Reverse Phase High Pressure Liquid Chromatography - Zulfikar, Z.; Antje, Labes (Indonesian Chimica Letters, 2022)
The present study has demonstrated the  HPLC method for identification and determination a and b-acids in Columbus hops. the measurement conditions has been set up included the use of Reverse phase C18 column Chromolith, gradient elution with methanol (A) and Acetonitril acidified with phosphate buffer at pH 2.8. While the flow rate has been applied of 0.8 mL/min, and it is run for 25 minutes. The separation of standard and sample has been monitored using UV variable detector in the rang of 300-340 nm. Pretreatment sample has been done using SPE with the cartridge of C18 similar to the analyte column. The results found that a four predominant peaks for α and β-acids, namely cohumulone (6.6 min), the second peak represents a mixture of humulone and adhumulone (8.9 min),  the third peak is colupulone (15.9 min) and the fourth is  a mixture of lupulone and adlupulone (16.7 min). The quantity of sample has been determined according to multipoint calibration using ICE2 standard, the sample found are 0,209 g/L cohumulone, 1.087 g/L of humulone and adhumulone, 0,349 g/L of Colupulone and 0.630 g/L of mixture of lupulone and adlupulone. In addition it is high precision measurement that is indicated by the value of RSD less than 1%.